Manganese- and Iron-Catalyzed Carbonylation Reactions: A Personal Account - Bao, Zhi-Peng; Wu, Xiao-Feng (Synlett, 2024)
Transition-metal-catalyzed carbonylative transformations have been widely employed to convert CO gas into valuable carbonyl-containing molecules, mainly using noble metals (Pd, Rh, Ir, Ru) and more recently nickel and other catalysts. Although noble-metal catalysts have the advantage of reaction efficiency, their high-cost has led scientists to explore alternative procedures. Also under these backgrounds, we carried out some studies on nonexpensive metal-catalyzed carbonylative transformations. In this Account, we summarize the carbonylation reactions developed in our research group by using manganese and iron catalysis. These carbonylation reactions proceeded either via SET (single-electron transfer) or TET (two-electron transfer) mechanism.1 Introduction2 Manganese-Catalyzed Carbonylation of Alkyl Chlorides3 Manganese-Catalyzed Carbonylation of Alkyl Iodides4 Iron/Copper-Catalyzed Carbonylation of Alkyl Bromides5 Iron-Catalyzed Carbonylation of Alkyl Bromides6 Iron-Catalyzed Carbonylation of Alkyl-Boronic Pinacol7 Iron-Catalyzed Aminoalkylative Carbonylative Cyclization of Alkenes8 Conclusion and Outlook
Keywords: carbonylation; manganese catalyst; iron catalyst; single-electron transfer; two-electron transfer